CRITICAL DISCOURSE ANALYSIS OF THE 'NON- NEGOTIABLE UNITY OF NIGERIA' DEBATE IN THE NIGERIAN PRESS - Ozioma, Nwokedi; Oluchukwu Nwabunze, Uzoma; Uchenna Eze, Ogemdi (African Journal of Social and Behavioural Sciences, 2024)
This present study interrogated the ‘non-negotiable unity of Nigeria’ mantra propagated in the media by successive administrations in Nigeria. With a particular focus on two administrations—President Goodluck Jonathan and President Muhammadu Buhari, this study, using Critical Discourse Analysis, examined how the debate is represented in two Nigerian dailies—Vanguard and Leadership. Employing Fairclough’s three-dimensional model, this research probed the discourse articulated and circulated through the news stories in these papers, which they produce to define the debate. The study found that both papers exploited the “us” versus “them” dichotomy to cut an image of institutions committed to Nigeria’s unity. The study constructs proponents of Nigeria's unity, primarily the political elite, in a positive light as possessing agency, while it negatively frames secessionist agitators as lacking agency. The study demonstrated that the interests of the political class served and validated. The research indicated that the press mobilised discourses of patriotism and nationalism. By reinforcing the non-negotiable stance of the political elite, the press was narrowing the space for debate on Nigeria’s unity, thus, perpetuating a dysfunctional union.